Lymph flow dynamics in exercising human skeletal muscle as detected by scintography - Havas, Eino; Parviainen, Tapani; Vuorela, Juha; Toivanen, Jarmo; Nikula, Tuomo; Vihko, Veikko (The Journal of physiology, 1997)
1. The effects of dynamic and isometric muscle contractions on the lymph flow dynamics in human skeletal muscle were studied with a scintographic method. 2. Radioactively labelled human serum albumin (99mTc-HSA) was injected bilaterally into the vastus lateralis muscles of eight men (n = 16), four of whom had had an endurance training background. The subjects performed 100 submaximal contractions in 10 min as (i) dynamic knee extensions (CONS), (ii) isometric contractions with the knees at full extension (IMExt), or (iii) isometric contractions with knees fixed at 90 deg angle flexion (IMFlex). The exercises were separated by 65 min periods in supine rest. The level of radioactivity at the injection site was monitored by a gamma-camera, and the clearance rate of radioactivity (CR) was calculated as the fractional decrease during the periods of interest (CR unit = % min-1). 3. The clearance rate was low during the rest periods (0.04 +/- 0.05% min-1), though higher in the trained than in the sedentary subjects (0.06 +/- 0.05 vs. 0.03 +/- 0.03% min-1; P = 0.008). Exercise increased the clearance rate three- to sixfold, to 0.16 +/- 0.16% min-1 during CONS, 0.20 +/- 0.15% min-1 during IMExt and 0.09 +/- 0.11% min-1 during IMFlex. There were no differences between the subject subgroups. 4. The higher clearance rate during IMExt than during IMFlex (P = 0.02) demonstrates the importance of muscle deformations on lymph propulsion and experimentally confirms the current concepts of lymph formation and propulsion in voluntarily active skeletal muscle. It is suggested that lymph propulsion by working muscle is most efficient when the muscle is able to shorten close to its minimum length.